Thymic Epithelial Cell Alterations and Defective Thymopoiesis Lead to Central and Peripheral Tolerance Perturbation in MHCII Deficiency - Ferrua, Francesca; Bortolomai, Ileana; Fontana, Elena; Di Silvestre, Dario; Rigoni, Rosita; Marcovecchio, Genni Enza; Draghici, Elena; Brambilla, Francesca; Castiello, Maria Carmina; Delfanti, Gloria; Moshous, Despina; Picard, Capucine; et al. (Frontiers in Immunology, 2021)
Major Histocompatibility Complex (MHC) class II (MHCII) deficiency (MHCII-D), also known as Bare Lymphocyte Syndrome (BLS), is a rare combined immunodeficiency due to mutations in genes regulating expression of MHCII molecules. MHCII deficiency results in impaired cellular and humoral immune responses, leading to severe infections and autoimmunity. The contribution of thymic epithelial cell (TEC) defects to the pathogenesis of this primary immunodeficiency has not been well characterized to date, in particular in regard to immune dysregulation. To this aim, we have performed an in-depth cellular and molecular characterization of TEC alterations in this disease. We observed an overall perturbation of thymic structure and function in both MHCII-/- mice and patients. Transcriptomic and proteomic profiling of murine TEC revealed several alterations. In particular, we demonstrated that impairment of lymphostromal cross-talk in the thymus of MHCII-/- mice affects mTEC maturation and promiscuous gene expression and causes defects of central tolerance. Furthermore, we observed peripheral tolerance impairment, likely due to defective Treg cell generation and/or function and B cell tolerance breakdown. Overall, our findings reveal disease-specific TEC defects resulting in perturbation of central tolerance and limiting the potential benefice of hematopoietic stem cell transplantation in MHCII deficiency.